Building structures : understanding the basics - Millais, Malcolm (London ; New York : Routledge, Taylor & Francis Group, 2017)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Preface to the Third Edition -- Introduction -- 0.1 Prehistoric design -- 0.2 Traditional design -- 0.3 The effect of civilisation -- 0.4 The search for structural understanding -- 0.5 The modern approach to structural design -- 0.6 The conceptual understanding of structural behaviour -- References - Introduction -- Chapter 1 Loads and load
Preface to the Third Edition. Introduction. 1. Loads and load paths. 2. Internal forces. 3. Structural element behaviour. 4. Advanced concepts of stress. 5. Structural materials. 6. Safe structures and failure. 7. Geometry and structural behaviour. 8. Below-ground structures. 9. Behaviour of a simple building. 10. Real structures. 11. Structural conception. 12. Structures and built form. 13. Structures in Existing Buildings. 14. A simple approach to calculations. 15. Dynamic Behaviour. 16. Progressive collapse and robustness. 17. The mathematical basis. 18. The basis for computer calculations. 19. The successful structural project. Further Reading. Index.
Includes bibliographical references and index.
ARC
Trim Education
Keywords: Buildings; Structural design; Structural analysis (Engineering); Architecture